Allelic Variants of the Adrb3 Gene and Their Interrelation with Indicators of the Morphenotype of Junior and Cadet Athletes (Eurasian Research Bulletin, 2022)
Today, it is especially important to timely identify the factors that determine the physical activity of athletes and help eliminate these factors. This, in turn, will help athletes achieve significant performance in sports and help preserve the health of junior and cadet athletes. Studies of the distribution of the ADRB3 gene polymorphism in those involved in such sports as athletics, cycling and swimming will allow us to carry out in the early stages a specialized selection of athletes predisposed to greater psychological stability and success.